Achieving social and economic development in africa through ecological and organic agricultural alternatives. Proceedings of the plenary presentations of the 3rd african organic conference. - (:unkn) unknown (My University, 2015)
This publication, Achieving Social and Economic Development in Africa through Ecological and Organic Agricultural Alternatives, is a follow up to FAO’s 2013 publication Organic Agriculture: African Experiences in Resilience and Sustainability. It follows firstly, because it reports on the progress made since the Lusaka Conference in 2012, but secondly, because it pushes forward our understanding of how ecological organic agriculture contribute not only to agricultural and ecosystem development, but also to social and economic developments. In Lagos, we learned that Ecological organic agriculture (EOA) “has a significant role to play in addressing the pressing problems of poverty, food insecurity, land degradation, market access, food safety and climate change in Africa. Ecological organic farming systems increase yields, are resilient to climate change effects and are cost-effective. Further, EOA is climate smart, preserves biodiversity, provides ecosystem services, and produces lower carbon emissions.” Both of these lessons remain pertinent to our ability to meet the new Sustainable Development Goals to eliminate global hunger and malnutrition. This publication gathers together in one volume the plenary papers presented during the Third African Organic Conference that took place in Lagos, Nigeria from 5-9 October, 2015. The different chapters document the institutional support that is developing across Africa to ensure that research, markets, and policies can contribute to the positive developmental impact of ecological organic agriculture. Together, they provide information about the status of ongoing initiatives to develop continent wide policy supports, national approaches and local innovations. A core theme of the event was the value of organic trade globally and the particular importance of focusing attention towards deepening access to national, regional and global markets for ecological and organic products. The topics addressed in this v
Keywords: African Research